Advantages of RNA‐seq compared to RNA microarrays for transcriptome profiling of anterior cruciate ligament tears. Issue 1 (29th August 2017) - Rai, Muhammad Farooq; Tycksen, Eric D.; Sandell, Linda J.; Brophy, Robert H.
ABSTRACT: Microarrays and RNA‐seq are at the forefront of high throughput transcriptome analyses. Since these methodologies are based on different principles, there are concerns about the concordance of data between the two techniques. The concordance of RNA‐seq and microarrays for genome‐wide analysis of differential gene expression has not been rigorously assessed in clinically derived ligament tissues. To demonstrate the concordance between RNA‐seq and microarrays and to assess potential benefits of RNA‐seq over microarrays, we assessed differences in transcript expression in anterior cruciate ligament (ACL) tissues based on time‐from‐injury. ACL remnants were collected from patients with an ACL tear at the time of ACL reconstruction. RNA prepared from torn ACL remnants was subjected to Agilent microarrays ( N  = 24) and RNA‐seq ( N  = 8). The correlation of biological replicates in RNA‐seq and microarrays data was similar (0.98 vs. 0.97), demonstrating that each platform has high internal reproducibility. Correlations between the RNA‐seq data and the individual microarrays were low, but correlations between the RNA‐seq values and the geometric mean of the microarrays values were moderate. The cross‐platform concordance for differentially expressed transcripts or enriched pathways was linearly correlated ( r  = 0.64). RNA‐Seq was superior in detecting low abundance transcripts and differentiating biologically critical isoforms. Additional independent validation of transcript expression was undertaken using microfluidic PCR for selected genes. PCR data showed 100% concordance (in expression pattern) with RNA‐seq and microarrays data. These findings demonstrate that RNA‐seq has advantages over microarrays for transcriptome profiling of ligament tissues when available and affordable. Furthermore, these findings are likely transferable to other musculoskeletal tissues where tissue collection is challenging and cells are in low abundance. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:484–497, 2018. Abstract : Transcriptome profiling of anterior cruciate ligament tears as a function of time‐from‐injury comparing microarrays to RNA‐seq showed that the cross‐platform concordance for differentially expressed transcripts or enriched pathways was linearly correlated ( r  = 0.64). RNA‐seq was superior in detecting low abundance transcripts and differentiating biologically critical isoforms. Thus, RNA‐seq is an extremely promising tool for the assessment of mRNA expression and identification of differentially expressed transcripts, comparable, and to some extent superior, to existing microarrays platforms in the analysis of ligamentous tissues.